PENGARUH PERMAINAN MODIFIKASI SOCCER BALL GAME TERHADAP MOTORIK HALUS PADA SISWA KELAS I SDN 101764 BANDAR KLIPPA - Khaira Saumina; Winara; Fahrur Rozi; Khairul Usman; Putra Afriadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of a modified Soccer Ball Game on the fine motor skills of first-grade students of SDN 101764 Bandar Klippa. This study used a quasi-experimental method with a Nonequivalent Control Group Design. The study sample consisted of 50 students, consisting of 25 students in the experimental class and 25 students in the control class. Data collection used a fine motor skills observation sheet that had been validated by experts and tested for inter-rater reliability. Data analysis was conducted using the Shapiro-Wilk normality test, Levene's homogeneity test, and hypothesis testing using the Independent Sample t-test using SPSS version 26. The results showed a significant effect of the modified Soccer Ball Game on the fine motor skills of first-grade students. This was evidenced by the Independent Sample t-test results, which obtained a calculated t-value of 4.617 with a significance value of 0.000 (p < 0.05), thus accepting the alternative hypothesis. Descriptively, the average posttest score for the experimental class was 13.48, higher than the 11.68 for the control class. Based on these results, it can be concluded that the modified Soccer Ball Game significantly improved the fine motor skills of first-grade students at SDN 101764 Bandar Klippa.